MOTIVASI WISATAWAN BERKUNJUNG KE DAERAH TUJUAN WISATA DANAU TOBA SUMATERA UTARA - Patricia L Sagala; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research done in the district of Samosir, exactly in Tomok Simanindo Sub-district. The goals in this research is: (a) analyzing the characteristics of the tourists visiting the tourist destination of Toba Lake, (b) analyzing the most dominant motivation attract tourists to visit tourist destination Toba Lake and tourist attraction is most preferred by tourists. The approach used in this research is quantitative, with quantitative analysis dekskriptif. From the research results obtained the conclusion that motivation to tourists visiting the tourist destination of Toba Lake that most dominant culture motivation namely, a) cultural performances, b) needs such as tourism attraction of art, indigenous peoples, dance, painting and religion. While from tourism attraction more dominant is the power pull the history tour, Eat Old King Sidabutar, Rock Wheelchair Trial Siallangan Museum and Tomok.Key Words : Motivation, Tourists